Connectors for electrical and electronic equipment. Product requirements. Power connectors. Detail specification for 2-pole or 3-pole power plus 2-pole signal shielded and sealed connectors with plastic housing for rated current of 40 A Part 8-101, (8th June 2020) - British Standards Institution,
No abstract available